PEMELIHARAAN LARVA HYBRID KERAPU CANTIK (Epinephelus sp) DI CV. JAYA UTAMA ABADI DESA KALIASEM, KECAMATAN BANJAR, KABUPATEN BULELENG, SINGARAJA BALI - Desilina Arif; Irawati Irawati; Shandy Rifta Aksan (Jurnal Perikanan Unram, 2024)
Hatchery technology for producing grouper seeds has developed widely and massively, one of which is to produce hybrid larvae. To produce beautiful hybrid grouper larvae, there are many factors that must be considered because they greatly influence the success of larvae production, including food management, water quality management and others. The purpose of writing this Final Practical Scientific Work Report is to find out the activities for rearing beautiful hybrid grouper larvae resulting from a cross between male batik grouper and female tiger grouper. Activities include egg handling, larval rearing, feed management, water quality management, grading and harvesting. Observations were carried out at the CV hatchery unit. Jaya Utama Abadi for 3 months from 15 February to 15 May 2021. Data obtained from survey activitieswith an apprenticeship pattern, namely taking part in rearing activities for beautiful hybrid grouper larvae. Primary data is collected through interviews and direct observation in the field, while secondary data is obtained through data or activity reports and other supporting literature, then processed.and analyzed quantitatively descriptively. Observation result The fertilized hybrid eggs are then hatched in a larval rearing tank using a volume of 6 m3 water of 5 unitswith a total number of eggs spread of 50,000 eggs/tub, or a total of 250,000 eggs, it produces an average hatchability of 54.4%, until they develop into 136,000 larvae and succeed in achieving a harvest with an average size of 3 cm/head of 11,900 eggs and a level of SR 88 %.